Partner-facilitating transmembrane penetration of nanoparticles: a biological test in silico. Issue 24 (13th June 2018) - Wang, W; Yang, R; Zhang, F; Yuan, B; Yang, K; Ma, Y
Abstract : Introducing a partner nanoparticle (NP) facilitates transmembrane penetration of a host NP due to membrane-mediated cooperation between them. Abstract : Transmembrane penetration of nanoparticles (NPs) promises an effective pathway for cargo delivery into cells, and offers the possibility of organelle-specific targeting for biomedical applications. However, a full understanding of the underlying NP–membrane interaction mechanism is still lacking. In this work, the membrane penetration behavior of NPs is statistically analyzed based on the simulations of over 2.2 ms, which are performed with dissipative particle dynamics (DPD). Influences from multiple factors including the NP concentration, shape and surface chemistry are taken into account. It is interesting to find that, the introduction of a partner NP would greatly facilitate the transmembrane penetration of a host spherical NP. This is probably due to the membrane-mediated cooperation between the NPs. Moreover, the proper selection of a partner NP with specific surface chemistry is of great significance. For example, the best partner for a hydrophilic NP to achieve transmembrane penetration is a Janus-like one, in comparison with the hydrophilic, hydrophobic or randomly surface-decorated NPs. Furthermore, such a partner-facilitating effect in NP translocation also works for a shaped NP although less pronounced. Our results are helpful for a better understanding of the complicated nano–bio interactions, and offer a practical guide to the NP-based drug delivery strategy with high efficiency.